IMPLEMENTASI KEBIJAKAN IDENTITAS KEPENDUDUKAN DIGITAL DALAM MENINGKATKAN EFISIENSI LAYANAN ADMINISTRASI KEPENDUDUKAN DI KOTA PEKANBARU PROVINSI RIAU - Indrian Syafitri; Annisa Mardatillah; Resti Hefriyenni (Pelantar Press, 2025)
This study aims to analyze the implementation of the Digital Population Identity (IKD) in improving the efficiency of population administration services in Pekanbaru City. The background of this research is based on the government’s efforts to transform public service systems toward effective, efficient, and accountable digital governance. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation at the Department of Population and Civil Registration (Disdukcapil) of Pekanbaru City. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the IKD in Pekanbaru City has had a positive impact on the efficiency of population administration services, particularly in accelerating service processes, reducing queues, and improving the accuracy of population data. However, several challenges remain, including limited public digital literacy, uneven network infrastructure, and the need to strengthen the capacity of human resources in managing digital systems. The study concludes that the success of IKD implementation largely depends on the synergy between technological readiness, human resource competence, and active community participation. Therefore, sustainable strategies are required to strengthen digital governance and realize more efficient and inclusive population administration services in the future.